SUMO proteases regulate ROS production in Arabidopsis - Conti, L.; Donnel, E.; Price, J.; Love, A.; Dominy, P.; Sadanandom, A. (Comparative Biochemistry and Physiology - Part A: Molecular & Integrative Physiology, 2007)
Plants have developed multiple strategies to cope with biotic and abiotic stress. A major goal of plant biology is to find how these stimuli are recognised, what signals they trigger and how they are integrated. Covalent protein modification plays a major role in cell signalling. Small Ubiquitin-like protein Modifiers (SUMO) are attached to key protein targets to modulate their activity. SUMO proteases convert proSUMO in the active form and remove SUMO from protein targets, a process which requires SUMO protease–target protein interaction. In plants, SUMO is involved in multiple signalling including pathogen resistance. OBS1 is a nuclear localised SUMO protease from Arabidopsis. Loss-of-function obs1 plants show increased thermotolerance compared to wild type. Heat shock perception requires OBS1 SUMO protease activity, as the ectopic expression of a protease deficient version of OBS1 phenocopies obs1 mutants. In contrast, OBS2 (the closest OBS1 homologue) knockouts or obs2/obs1 double mutants are hyper heat-sensitive suggesting that OBS1 and OBS2 act in the same pathway, but have opposite roles. Salicylic acid (SA) has been linked to heat tolerance and OBS1 and OBS2 are SA inducible. When sprayed with SA, obs1 plants produce a reduced oxidative burst compared to wild type, while obs2 and obs1/obs2 double mutants show an enhanced oxidative burst. These results suggest a molecular model whereby OBS1 modulates OBS2 activity to trigger the oxidative burst. Given the key role of the oxidative burst in plant stress responses, our data indicate that OBS1/OBS2 may play a key role in biotic and abiotic signalling.